The indigenous community’s perceptions of tourism development in the Cameron Highlands, Malaysia: a preliminary study / … [et al.] - Mohd Salleh, Norlida Hanim; Othman, Redzuan; Mohd Idris, Siti Hajar; Jaafar, Abdul Hamid; Selvaratnam, Doris Padmini (Universiti Teknologi MARA (UiTM), Malaysia, 2012)
The development of the tourism industry in the Cameron Highlands has brought many positive impacts directly or indirectly to the local community in general, including the minority group of indigenous people. The main purpose of the study is to analyze the general socio-economic and environmental impacts upon the indigenous community as a result of tourism development in the Cameron Highlands. This analysis is based on their perceptions of three aspects, namely economic, social and environmental issues due to tourism development. Face to face interviews with selected respondents using the stratified random sampling method were undertaken during October-November 2011 in the village of Sungai Ruil indigenous community. A total of 90 respondents were interviewed. Research findings show that the development of the tourism industry has created positive impacts on these three aspects for the indigenous communities in Sungai Ruil. The results also revealed that in comparison the social impact is greater than the economic and environmental impacts.